Distribution and economic analysis of Prosopis juliflora in Ethiopia - Wakie, Tewodros T., author; Laituri, Melinda, advisor; Evangelista, Paul, advisor; Hoag, Dana, committee member; Jarnevich, Catherine, committee member (Colorado State University. Libraries, 2015)
Invasive species are one of the drivers of biological and socio-economic changes around the world. Over the past 30-40 years, the non-native Prosopis juliflora plant has emerged as a major invader of the arid and semi-arid regions of Ethiopia. Information on its distribution, impact, use and management is highly needed to contain and prevent the spread of this highly invasive plant. In the first study, I used a correlative modeling framework to track and map the current and potential distribution of P. juliflora in Afar, north-eastern Ethiopia. Specifically, I used time-series of Moderate Resolution Imaging Specrtoradiometer (MODIS) satellite imagery, 143 species-occurrence records and the Maxent modeling technique to map its current distribution. I then used topo-climatic predictors, species-occurrence records and the Maxent software to map its forecasted distribution. I found that the current extent of P. juliflora invasion in the Afar region is approximately 3,605 Km2, while its predicted distribution is approximately 5,024 Km2. My findings demonstrates that MODIS vegetation indices and species-occurrence points can be used with Maxent modeling software to map the current distribution of P. juliflora, while topo-climatic variables are good predictors of its potential habitat in Ethiopia. In the second study, I used a participatory research framework to map P. juliflora over a fine geographic scale, and to identify the major resource related problems in the region. I learned about the introduction history, spread, impacts, uses and traditional management practices of P. juliflora in Afar by interviewing 108 pastoralists and agro-pastoralists. Additionally, I detected the land-cover categories most affected by P. juliflora invasion by superimposing community produced maps on ancillary land-cover layers, and performing overlay analysis. Prosopis juliflora has highly invaded grasslands and open areas in Afar. The species displaces useful native grass and forage species, which are important for sustaining the region's wildlife and livestock resources. In addition to threats from invasive species, Afar people face conflicts from neighboring Issa ethnic groups, and land-grabs from the central government and foreign investors. The findings demonstrates that participatory mapping methods are suitable for mapping species distribution, detecting land-cover changes, and managing invasive plants. High invasive species control costs have swayed most developing countries to adopt cost effective P. juliflora eradication and utilization practices. However, the effectiveness and economic viability of these new approaches have not been thoroughly tested. In the third study, I used an economic analysis framework to assess the economic feasibility of selected P. juliflora eradication and utilization methods that are practiced in southern Afar. The dominant P. juliflora eradication option was to convert infested lands into irrigated farms, while the preferred utilization options were to make animal fodder from P. juliflora seed pods, and to produce charcoal from P. juliflora wood. I interviewed 19 enterprise owners (i.e., farmers, flour producers and charcoal makers) and collected primary data on prices, yields, costs and revenues. I assessed the economic feasibility of the selected methods by performing enterprise, profitability, sensitivity and risk analyses over 10 years and an interest rate of 10% per year. Converting P. juliflora infested lands into irrigated agriculture is a profitable and risky P. juliflora eradication approach. Charcoal making is a moderately profitable and less risky utilization approach, while flour production is a risky and an un-profitable utilization approach. Introducing new changes in the production and management steps of flour production may be needed to make flour enterprises profitable. My overall economic analysis suggests that control through utilization may be one of the effective and economically viable P. juliflora management strategies currently accessible to Ethiopia. I generated reliable information on the distribution and impacts of P. juliflora in Afar by employing a wide variety of scientific approaches. My results can guide local level P. juliflora utilization and control efforts in Afar, while my methodologies can be replicated for managing invasive plants in other developing countries.
Keywords: correlative models; economic analysis; Ethiopia; invasive species; participatory research; Prosopis juliflora